Analysis of scientific production on the new coronavirus (COVID-19): a bibliometric analysis - Oliveira, Erika Morganna Neves de; Carvalho, Ana Raquel Batista de; Silva, Joyce Soares e; Sousa Neto, Antônio Rosa de; Moura, Maria Eliete Batista; Freitas, Daniela Reis Joaquim de (São Paulo Medical Journal, 2021)
BACKGROUND: The pandemic of the new coronavirus has culminated in a scientific race to seek knowledge about this virus and its treatments, vaccines and preventive strategies, in order to reduce its impact on healthcare and economics worldwide. Hence, it is important to recognize the efforts of researchers who are at the forefront of investigations relating to the new coronavirus. OBJECTIVE: The present study was carried out with the aim of analyzing the world scientific production relating to COVID-19. DESIGN AND SETTING: Exploratory and descriptive bibliometric study conducted in the city of Teresina (PI), Brazil. METHOD: ISI Web of Knowledge/Web of Science (WOS) was chosen as the database. Data-gathering was carried out in May 2020. The data analysis was performed using the HistCiteTM software, version 9.8.24, and the VOSviewer bibliometric analysis software, version 1.6.8. RESULTS: 2,625 published papers that included descriptors within the scope of this investigation were identified. These articles were published in 859 different journals that are indexed in WOS, by 9,791 authors who were linked to 3,365 research institutions, located in 105 countries. CONCLUSION: Ascertaining scientific production through a bibliometric analysis is important in order to guide researchers on what has already been produced and what is being researched, so as to be able to address gaps in knowledge through future research.